Selective Recovery of Scandium from Titanium Ores in Complex Multi-metal Systems - Caroline Strnad; Michael Lechner; Helmut Flachberger; Eva Gerold (BHM Berg- und Hüttenmännische Monatshefte, 2026)
Scandium (Sc) is classified as a critical and strategic raw material due to its applications in the aerospace industry and in modern energy systems. As scandium rarely forms independent minerals, it accumulates in secondary streams. This article describes a conceptual process, which can be integrated into existing titanium processes, for the selective recovery of scandium from chloride-rich hydrolysis solutions from titanium dioxide production (approx. 25 mg/l Sc). The greatest challenge lies in the similar chemical behaviour of scandium compared to iron and titanium, which complicates selective separation. The key point is that selectivity depends less on the extractants than on the control of metal species, particularly iron, within the complex multi-metal system. The reduction of Fe 3 ⁺ to Fe 2 ⁺ (e.g., using ascorbic acid or iron powder) significantly suppresses the co-extraction of iron in organophosphorus-based SX systems but, at the same time, requires the control of reduced titanium species (e.g., Ti 3 ⁺). Solvent extraction with D2EHPA serves as the main separation step. Synergistic systems with defined TBP fractions improve phase stability and reduce emulsion formation during high Sc extraction. The process route comprises the following steps: (i) redox pre-treatment, (ii) solvent extraction or, alternatively, ion exchange at low pH, (iii) HCl scrubbing, alkaline stripping, redissolution and precipitation (e.g., with oxalate), followed by calcination to produce Sc 2 O 3 , and (iv) utilisation of the by-products (Fe, Ca). Selective iron precipitation is not possible as Sc precipitates completely at a pH of around 5, and therefore redox control takes priority. Overall, the approach demonstrates that an efficient value creation from scandium is possible within existing titanium production routes. However, the validation of the key mechanisms and scalability still need to be confirmed experimentally.

Mineralogical Characterization and Recovery Potential of Zircon and Phosphate Minerals from Ilmenite-rich Heavy Mineral Sand Tailings - Michael Lechner; Caroline Strnad; Eva Gerold; Helmut Flachberger (BHM Berg- und Hüttenmännische Monatshefte, 2026)
This article investigates the mineralogical characteristics and beneficiation potential of zircon and phosphate minerals in ilmenite-rich heavy mineral sand tailings from a Ukrainian deposit. Based on a comprehensive fractional class analysis, it is observed that a significant enrichment of zircon, monazite, and xenotime occurs in the fine fraction (

Processing of Ukrainian Ilmenite-bearing Heavy Sands as a Contribution to Improving Europe’s Self-supply in Critical Raw Materials from Its Own Deposits - Michael Lechner; Eva Gerold; Helmut Flachberger (BHM Berg- und Hüttenmännische Monatshefte, 2025)
The REPTiS project ( R esponsible E xtraction and P rocessing of Ti tanium and Other Primary Raw Materials for S ourcing EU Industrial Value Chains and Strategic Sectors) addresses the urgent need for a secure and sustainable supply of titanium and other critical raw materials (CRMs) within the EU. Given the EU’s dependency on imports and the risks of supply chain disruptions, REPTiS focuses on the responsible extraction and processing of titanium and other CRMs from heavy mineral sands. The main aim of this dissertation is to optimize the current beneficiation process in Ukraine to enhance ilmenite (FeTiO 3 ) recovery while developing new approaches for extracting valuable by-products such as rare earth elements, niobium, tantalum, and scandium. Further, a whole new processing scheme for unused weathering crust sands will be developed and implemented in the beneficiation process. Additionally, the potential use of kaolinite as an additive feedstock in the concrete industry will be evaluated.

Sentinel-2 vs. PlanetScope: Comparison and combination for tree species classification in two central European forest ecosystems - Ardalan Daryaei; Michael Lechner; Anna Iglseder; Lars T. Waser; Markus Immitzer (Remote Sensing Applications: Society and Environment, 2025)

The carnivoran guilds from the Late Miocene hominid locality of Hammerschmiede (Bavaria, Germany) - Nikolaos Kargopoulos; Alberto Valenciano; Juan Abella; Michael Morlo; George E. Konidaris; Panagiotis Kampouridis; Thomas Lechner; Madelaine Böhme (Geobios, 2025)

Enrichment of a dioxin‐dehalogenating Dehalococcoides species in two‐liquid phase cultures - Michael Bunge; Anke Wagner; Marco Fischer; Jan R. Andreesen; Ute Lechner (Environmental Microbiology, 2008)
Summary Enrichment cultures capable of reductively dechlorinating 1,2,4‐trichlorodibenzo‐ p ‐dioxin (1,2,4‐TrCDD) were shown to dechlorinate 1,2,3‐trichlorobenzene (1,2,3‐TrCB) to 1,3‐dichlorobenzene. To test if this activity can be used to enrich for dioxin‐dechlorinating bacteria, a two‐liquid phase cultivation with 200 mM 1,2,3‐TrCB dissolved in hexadecane was established. During the dechlorination of 1,2,3‐TrCB, the number of 1,2,4‐TrCDD‐dechlorinating bacteria increased by four orders of magnitude, eventually accounting for 11% of the total cell number. Characterization of the bacterial communities of the initial dioxin‐dechlorinating culture and of the trichlorobenzene enrichments by restriction fragment length polymorphism (RFLP) analysis of cloned 16S rRNA genes revealed a proportional increase of nine different sequence types, one representing a Dehalococcoides strain. Inhibition of methanogens further enhanced the rate of chlorobenzene dehalogenation and also resulted in a rapid dechlorination of 1,2,3,4‐tetrachlorodibenzo‐ p ‐dioxin that was applied via a hexadecane phase . The further enrichment was monitored by terminal RFLP, quantitative real‐time PCR and microscopy, and aimed at the reduction of the accompanying non‐dehalogenating populations by using different combinations of electron donors and the application of antibiotics. Hydrogen as the sole electron donor proved to be less efficient due to the co‐enrichment of acetogens. The novel Dehalococcoides strain DCMB5 was enriched up to 50% by the cultivation with organic acids, hydrogen and vancomycin, and was finally purified by conventional isolation techniques.

Biological Activity in a Heavily Organohalogen-Contaminated River Sediment (8 pp) - Michael Bunge; Mika A. Kähkönen; Winfried Rämisch; Matthias Opel; Susanne Vogler; Fred Walkow; Mirja Salkinoja-Salonen; Ute Lechner (Environmental Science and Pollution Research, 2007)